Substantiation of methodological approaches to compiling complex recreational programs - Oleksandr Aghyppo (Kharkiv State Academy of Physical Culture, 2018)
Purpose: substantiation of methodological approaches to compiling up recreational programs, as a form of activity of a specialist in the field of physical education. Material & Methods: analysis of available literature and system analysis. Results: analysis of the peculiarities of recreation and health improvement allowed substantiating the content of the corresponding recreational and recreational programs. Conclusions: the core of these programs should be a modified mode of the day, a significant place in them occupies food and motor activity. The organization of recreation and health improvement of children belonging to 1-2 groups of health also needs to make changes and additions that take into account the state of health, the fulfillment of hygiene requirements, and the correction of the main components of recreational and recreational systems. This will ensure adequate and effective optimization of schoolchildren's health.